2019
DOI: 10.2478/bhk-2019-0010
|View full text |Cite
|
Sign up to set email alerts
|

Student-centered approach and alternative assessments to improve students’ learning domains during health education sessions

Abstract: SummaryStudy aim: The purpose of this study was to evaluate the effects of astudent-centered approach and alternative assessments on students’ learning domains (i.e., cognitive, affective, psychomotor) during health education learning sessions.Material and methods: Four groups totaling 65 mixed-gender undergraduate students (ages 20–25) of physical and health education participated in this study of alternative assessments’ effects on students’ learning once per week (3 hours) in their respective classrooms for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…It is being queried if past methods of tertiary teaching are still relevant, effective and engaging for adults that have grown up in a digital age. To encourage a higher level of student engagement there have been suggestions that healthcare curricula should move from the traditional lecturer-led approach to become more student-centred ( 47), including such techniques as the flipped classroom (48) and peer teaching (47). Although attendance to the smaller, more student-centred sessions in the paramedic course such as tutorials or practical skills were not measured, data from our interviews indicate that students may be more likely to attend these forms of education compared with lectures.…”
Section: Discussionmentioning
confidence: 99%
“…It is being queried if past methods of tertiary teaching are still relevant, effective and engaging for adults that have grown up in a digital age. To encourage a higher level of student engagement there have been suggestions that healthcare curricula should move from the traditional lecturer-led approach to become more student-centred ( 47), including such techniques as the flipped classroom (48) and peer teaching (47). Although attendance to the smaller, more student-centred sessions in the paramedic course such as tutorials or practical skills were not measured, data from our interviews indicate that students may be more likely to attend these forms of education compared with lectures.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that demonstrates the efficacy of providing participants with self-monitoring tools in increasing motivation to participate in PA, enhancing self-monitoring skills and thus, greater awareness around goal behaviour discrepancy to improve their lifestyles [69,70]. There were four studies that utilised this intervention type [71][72][73][74].…”
Section: Self-monitoring Toolsmentioning
confidence: 99%
“…Finally, the third study that was effective in increasing PA levels using this intervention type provided participants with pedometers to track and provide feedback on their daily step count [74]. While the last study [71] mentioned an increase in the number of weekly recorded pedometer steps from 59,560 to 87,286 after seven weeks of their intervention, there was no significant testing and thus the study was marked as not being effective However, given the study's results, the success of the intervention by [74] and the similarities across the two interventions, there is reason to believe that the study would have been found to be effective if statistical testing were done.…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation